X-ray imaging of spin currents and magnetisation dynamics at the nanoscale. (21st February 2017) - Bonetti, Stefano
Abstract: Understanding how spins move in time and space is the aim of both fundamental and applied research in modern magnetism. Over the past three decades, research in this field has led to technological advances that have had a major impact on our society, while improving the understanding of the fundamentals of spin physics. However, important questions still remain unanswered, because it is experimentally challenging to directly observe spins and their motion with a combined high spatial and temporal resolution. In this article, we present an overview of the recent advances in x-ray microscopy that allow researchers to directly watch spins move in time and space at the microscopically relevant scales. We discuss scanning x-ray transmission microscopy (STXM) at resonant soft x-ray edges, which is available at most modern synchrotron light sources. This technique measures magnetic contrast through the x-ray magnetic circular dichroism (XMCD) effect at the resonant absorption edges, while focusing the x-ray radiation at the nanometre scale, and using the intrinsic pulsed structure of synchrotron-generated x-rays to create time-resolved images of magnetism at the nanoscale. In particular, we discuss how the presence of spin currents can be detected by imaging spin accumulation, and how the magnetisation dynamics in thin ferromagnetic films can be directly imaged. We discuss how a direct look at the phenomena allows for a deeper understanding of the the physics at play, that is not accessible to other, more indirect techniques. Finally, we present an overview of the exciting opportunities that lie ahead to further understand the fundamentals of novel spin physics, opportunities offered by the appearance of diffraction limited storage rings and free electron lasers.